2011
DOI: 10.1088/0964-1726/20/7/075004
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-electro-mechanical instability of dielectric elastomers

Abstract: We here propose a new method to analyze the thermo-electro-mechanical instability of dielectric elastomers. The equilibrium equations in this thermodynamic system at different temperatures are initially established. We then obtained the critical nominal electric field and the critical stretch under various mechanical and thermal loads, involving the effects of different stretch regimes on the system stability, i.e. the equal-biaxial stretch, the unequal-biaxial stretch and the thickness elongation. Finally, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Thank to equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), this energy can be computed. One can note that the pull-in instability is not occuring for Polypower elastomer thanks to its low chain extension limit and low dielectric strength as investigated in.…”
Section: Operating Limits For Dielectric Elastomer Generatorsmentioning
confidence: 99%
“…Thank to equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), this energy can be computed. One can note that the pull-in instability is not occuring for Polypower elastomer thanks to its low chain extension limit and low dielectric strength as investigated in.…”
Section: Operating Limits For Dielectric Elastomer Generatorsmentioning
confidence: 99%
“…Recent studies have shown when the DE membrane is infiated by air, the voltage-induced area expansion can be up to 1689% [16], and multiphase coexistence is observed [17]. However, high voltage has to be kept to maintain the strokes of DE actuators, which limits their practical application [6,18].…”
Section: Introductionmentioning
confidence: 99%
“…Electromechanical instabilities are harnessed to enhance the performances of DE actuators, including achieving large voltageinduced actuation [16,20] and multiphase coexistence [17]. In these approaches, DE actuators still require keeping the voltage to maintain their strokes [6,18,[22][23][24][25], which leads to high energy consumption and device failures [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study indicated that the increase in temperature can markedly contribute to improving the entropy production and the critical nominal electric field of the DE [17] . Recently, Liu et al [18] studied the thermo-electro-mechanical instability of dielectric elastomers by employing a Mooney-Rivlin model, but used independently determined value for the dielectric constant. In fact, recent experiments on a VHB 4910 dielectric elastomer have shown that the dielectric constant drops linearly as area pre-strain increases at different temperatures and dielectric constant of the polymer is a function of temperature [19] .…”
Section: Introductionmentioning
confidence: 99%